2020
DOI: 10.21203/rs.3.rs-28883/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fast and low-cost detection of SARS-CoV-2 peptides by tandem mass spectrometry in clinical samples

Abstract: The current outbreak of severe acute respiratory syndrome associated with coronavirus 2 (SARS-CoV-2) is pressing public health systems around the world, and large population testing is a key step to control this pandemic disease. Real-time reverse-transcription PCR (real-time RT-PCR) is the gold standard test for virus detection but the soaring demand for this test resulted in shortage of reagents and instruments, severely limiting its applicability to large-scale screening. To be used either as an alternative… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…The major advantage of our method is its short run time with a 2.3 min gradient which is the fastest reported till date for detection of SARS-CoV-2 peptides. Cardozo et al (2020) reported a MRM with a gradient of 10.5 min that could detect SARS-CoV-2 peptides with a sensitivity of 83%. Interestingly, they used fully automated sample preparation protocol using robotic liquid handler and turbulent flow chromatography, multiplexed for online sample clean-up and UPLC separation that enabled them to run 4 samples within the 10.5 min run.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major advantage of our method is its short run time with a 2.3 min gradient which is the fastest reported till date for detection of SARS-CoV-2 peptides. Cardozo et al (2020) reported a MRM with a gradient of 10.5 min that could detect SARS-CoV-2 peptides with a sensitivity of 83%. Interestingly, they used fully automated sample preparation protocol using robotic liquid handler and turbulent flow chromatography, multiplexed for online sample clean-up and UPLC separation that enabled them to run 4 samples within the 10.5 min run.…”
Section: Discussionmentioning
confidence: 99%
“…They also shortlisted several peptides for targeted mass spectrometric studies (Gouveia et al 2020). Cardozo et al have reported the detection of three peptides using a 10.5 min run time with 83% sensitivity and 96% specificity (Cardozo et al 2020). Ihling et al used a gargle solution of 3 infected patients and report the identification of 1 peptide from nucleoprotein using a 180 min gradient (IIhling et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For establishing workflows to evaluate virus-specific peptides, three published cell culture datasets [22][23][24] which used SARS-COV2 infected Vero cell lines were chosen, along with five clinical datasets [25][26][27][28][29] .…”
Section: Case Studymentioning
confidence: 99%
“…In order to evaluate the most robustly detectable SARS-CoV-2 peptides, and make the detection of these viral peptides in human samples in a clinical setting all the more feasible, we set out to examine proteomic datasets from three cell culture-based studies [22][23][24] and five clinical studies [25][26][27][28][29] . We utilized automated workflows implemented in the Galaxy platform and made accessible via the European Galaxy public instance to first identify as many SARS-CoV-2 peptides possible in all samples, creating a master list of SARS-CoV-2 peptides identified across the samples.…”
Section: Introductionmentioning
confidence: 99%
“…The TFC comprised a four‐time multiplexed online sample clean‐up and ultra‐performance liquid chromatography separation. The method was validated using 562 specimens that had been previously analyzed by RT‐PCR and detected over 83% of the positive cases (Cardozo et al, 2020). In another example, a number of different methods were assessed for quantitative measurement of metallodrug–protein interactions.…”
Section: Alternative Technologiesmentioning
confidence: 99%